Enhancing Community Resilience in Facing Terrorism Threat in Indonesia : Sociological Perspectie - Agni, Wanti; Priyanto, Priyanto; Pitoyo , Ari (CV. AFDIFAL MAJU BERKAH, 2025)
Terrorism has caused a national security crisis in Indonesia, which is very dangerous for our country because it affects all citizens, both government and civilians. The purpose of this study is to determine the factors causing the emergence of terrorism and the role of civil society in preventing the spread of terrorism in Indonesia. The research method used to meet the research objectives is a qualitative method, through literature review, research results published in print media, and national and international journals. The results of the study show several factors causing the emergence of terrorism. Based on sociological review, there is the influence of social media on young people, feelings of marginalization (a sense of being excluded) and differences in ideology and social networks. Social participation by civil society in facing terrorism can be developed through the active conduct of community activities starting from their surroundings. The importance of cooperation between government and civil society is also a focus in this sociological analysis. Close collaboration between these parties is expected to create a conducive environment for building awareness, education, and joint efforts in combating terrorism. The involvement of civil society in programs for preventing radicalization, training, and rehabilitation can form a strong network in supporting efforts to prevent terrorism